Katya Krylova. The Long Shadow of the Past: Contemporary Austrian Literature, Film, and Culture. Camden House, 2017. - Laura McLary (Studies in 20th & 21st Century Literature, 2019)
Review of Katya Krylova. The Long Shadow of the Past: Contemporary Austrian Literature, Film, and Culture. Camden House, 2017.
Keywords: Austria; post-Holocaust; post-Waldheim